County-Level Economic Development Mode in the Context of China’s Rural Revitalization: A Fuzzy-Set Qualitative Comparative Analysis - Yiting Wu; Yunqing Liu; Zekun Dai; Fang Da (SAGE Open)
In the context of China’s rural revitalization strategy, the significance of county economic development cannot be overstated. Aligning county economic development with the deeper implications of this strategy is a pressing concern for governments at every level. This study, drawing from the Technology-Organization-Environment (TOE) framework, employs the fs-QCA method to elucidate the causal mechanisms underpinning high-quality county-level economic development. Utilizing data from 57 counties in an agricultural province in China, this research investigates the interplay between antecedent conditions and county economic development, delineating distinct developmental pathways that yield optimal outcomes. The findings reveal that, (1) no singular condition suffices to attain superior county economic development; rather, it emerges from the confluence of multiple factors. (2) Four distinct pathways, technology-led industry-pull, technology-driven government-supported, all-factor linkage, and technology-organized balanced, are instrumental in achieving high-level county economic development. (3) Substitutional relationships exist among the antecedent conditions. These insights deepen our comprehension of the multifaceted determinants influencing county economic growth. By highlighting the interdependencies among these conditions, this research offers valuable perspectives that can guide the formulation of pragmatic, synergistic policies, paving the way for efficient county economic developmental trajectories.